Generating matrix and sums of Fibonacci and Pell sequences - Ho C.K.; Woon H.S.; Chong C.-Y. (American Institute of Physics Inc., 2023)
In this paper, we study the Fibonacci sequence and Pell sequence and developed generating matrices for them. First we proved two results on the even sum of the Fibonacci sequence and the Pell sequence, using the generating matrix approach. We then deduce the odd sums, some identities and recursive formulas for these two sequences. © 2014 AIP Publishing LLC.